Practice of Writing Death Certificates in Different Medical College Hospitals of Bangladesh (Bangladesh Journal of Medical Education, 2025)
Background: Accurate death certification is essential for legal, administrative, and public health functions. However, errors in completing death certificates can undermine the reliability of mortality data. Objectives: This study aimed to assess the quality of death certificate completion in medical college hospitals across Bangladesh, identify common errors, and explore underlying causes and potential solutions. Methods: An observational cross-sectional study was conducted using two data sources: A review of 400 death, certificates from hospital records. Evaluation of 100 death certificates completed by physicians in response to a dummy case scenario. Additionally, in-depth interviews were conducted with senior faculty members to gain insights into existing practices and improvement strategies. Results: Among hospital records, 64% of certificates listed ill-defined conditions as the underlying cause of death, with cardiorespiratory failure being the most frequently cited. Sequence errors were present in 50% of hospital-record certificates and also prevalent in dummy case responses, though at a lower rate. Interviews revealed a lack of training, feedback, and standardized procedures as key contributors to errors. Conclusion: The study highlights substantial deficiencies in the accuracy of death certification practices in Bangladesh. Structured training, routine feedback, and the adoption of digital certification systems are recommended to improve the quality and reliability of mortality data.BJME, Volume-16, Issue-02, July 2025: 24-28